Research Progress on Sleep Regulatory Factors and Their Dietary Sources - Hangqing ZHOU; Guifang ZHANG; Shanshan LI; Rong ZHU; Dongjie ZHANG (Shipin gongye ke-ji)
Sleep disorders can lead to various diseases, so good sleep plays an important role in maintaining the physiological and psychological health of all living organisms. Compared with traditional medicines, dietary intake has a higher safety factor in improving sleep and does not cause drug dependence in people. This article first summarizes the functional factors related to regulating sleep from three aspects: excitatory and inhibitory neurotransmitters, immune cytokines, and gut microbiota. Secondly, the mechanisms of action of different sleep regulating factors are reviewed. Finally, the dietary sources of different sleep regulating factors are summarized, in order to provide theoretical support for the industrialization and commercialization of functional foods for improving sleep in the future.